2022
DOI: 10.3390/ijerph192215180
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Culturally Specific Male Domestic Violence Offender Intervention Programs on Behavior Changes and Mental Health: A Systematic Review

Abstract: The objective of domestic violence intervention programs is to address perpetrator behavior. However, the suitability and effectiveness of these programs in confronting problematic behavior for ethnically diverse groups is unclear. Therefore, the aim of this systematic review was to cohesively examine whether such programs are effective in reducing recidivism, changing perpetrator behavior, and addressing mental health issues for culturally diverse groups. Several databases were searched for peer-reviewed arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(170 reference statements)
1
5
0
Order By: Relevance
“…We identified 23 systematic reviews/ meta-analytic evaluations of trials on the effects of male perpetrator programmes ( Akoensi et al, 2013 ; Aos et al, 2006 ; Arce et al, 2020 ; Arias et al, 2013 ; Babcock et al, 2004 ; Cheng et al, 2021 ; Feder et al, 2008 ; Feder & Wilson, 2005 ; Ferrer-Perez & Bosch-Fiol, 2018 ; Karakurt et al, 2019 ; Miller et al, 2013 ; Nesset et al, 2019 ; NICE, 2013 ; O’Connor et al, 2021 ; Pinto E Silva et al, 2022 ; Santirso et al, 2020 ; Satyen et al, 2022 ; Smedslund et al, 2011 ; Stephens-Lewis et al, 2021 ; Tarzia et al, 2020 ; Travers et al, 2021 ; Vigurs et al, 2016 ; Wilson et al, 2021 ). These 23 systematic reviews and meta-analyses were used to identify primary studies evaluating IPV perpetrator programmes, which is the main focus of this paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 23 systematic reviews/ meta-analytic evaluations of trials on the effects of male perpetrator programmes ( Akoensi et al, 2013 ; Aos et al, 2006 ; Arce et al, 2020 ; Arias et al, 2013 ; Babcock et al, 2004 ; Cheng et al, 2021 ; Feder et al, 2008 ; Feder & Wilson, 2005 ; Ferrer-Perez & Bosch-Fiol, 2018 ; Karakurt et al, 2019 ; Miller et al, 2013 ; Nesset et al, 2019 ; NICE, 2013 ; O’Connor et al, 2021 ; Pinto E Silva et al, 2022 ; Santirso et al, 2020 ; Satyen et al, 2022 ; Smedslund et al, 2011 ; Stephens-Lewis et al, 2021 ; Tarzia et al, 2020 ; Travers et al, 2021 ; Vigurs et al, 2016 ; Wilson et al, 2021 ). These 23 systematic reviews and meta-analyses were used to identify primary studies evaluating IPV perpetrator programmes, which is the main focus of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…We searched broadly using eight electronic databases. Previous systematic reviews and/or meta-analyses used between two and six databases except for one article that used 13 databases to assess cultural differences in IPV interventions ( Satyen et al, 2022 ). Although our review used multiple databases it does not fulfil the search criteria for a systematic review ( Uman, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…India, a multicultural nation, requires interventions tailored to specific cultural contexts. [ 64 ] Such culture-based interventions provide valuable insights for professionals and survivors, improving studyoutcomes. [ 65 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that assess reoffense through these measures generally have revealed positive outcomes (e.g., Cunha & Gonçalves, 2015;Lila et al, 2018). For example, a systematic review that examined the effectiveness of culturally specific male PIPs found that the two studies that assessed recidivism through self-reports revealed significant reductions in episodes of abuse (Satyen et al, 2022). Cunha and Gonçalves (2015), comparing 26 individuals who attended intervention with 19 individuals who did not, found that those who attended a PIP self-reported significantly less abusive behaviors than the control group.…”
Section: Abusive Behavior and Recidivismmentioning
confidence: 99%